A Case Of Abdominal Ectopic Pregnancy To Term With Favorable Evolution Mother Child - admin, admin (2018)
Abdominal ectopic pregnancy is extremely rare and dangerous, without making a proper diagnosis and early treatment, leads to high maternal fetal and where the possibility of coming to term are remote and fetal survival even more so. In the last decades has increased the frequency of abdominal ectopic pregnancy which is 1 per 10000. We report the case of a pregnant woman with abdominal ectopic pregnancy to term with live fetus reaching emergency service, Critical Care Department of Maternal and Perinatal Institute during the hospital guard, which is operated and progressing well, both mother and child. We present graphic evidence of it.